Investigation of the Reasons for the Non‐Return of Lapsed Blood Donors: A Qualitative Study - Hayedeh Javadzadeh Shahshahani; Mojtaba Fattahi Ardakani; Farahnaz Amiri; Sadegh Kazemi; Sara Heydari; Moradali Zareipour; Seied Mohamadreza Aghaee Meybody; Hossein Rointan; Mahatab Vaziri (Health Science Reports, 2026)
ABSTRACT Background and Aims Retaining and re‐engaging blood donors to ensure a safe and sufficient blood supply is a key responsibility of the Blood Transfusion Organization. This study aimed to investigate the reasons for the non‐return of lapsed blood donors to facilitate their re‐engagement. Methods This qualitative study, conducted in 2024, employed a conventional content analysis approach using four focused group discussions (FGDs) and individual interviews with seven lapsed blood donors selected purposefully. The credibility and reliability of the qualitative data were ensured through techniques such as maximum variation sampling, member checking, peer review, and the use of participant quotes. The interviews were recorded, manually coded, and categorized. Data analysis was carried out using Colaizzi's seven‐step method. Results In total, 34 individuals participated in this study. The reasons for non‐return included 94 initial codes, 26 subcategories, and 8 categories (medical and non‐medical health‐related reasons, life responsibilities, changes in attitude toward blood donation, blood donation with others, desire to perform wet cupping for ideological reasons and community recommendations, beliefs about blood donation, organizational limitations, and cultural awareness). These were grouped into three main themes: individual reasons, social determinants of blood donation, and social marketing of blood donation. Conclusion By understanding the individual needs of donors, community beliefs, and expectations, it is possible to promote a culture of blood donation through appropriate advertising and the production of up‐to‐date content in governmental and social media.